2014
DOI: 10.1002/dev.21237
|View full text |Cite
|
Sign up to set email alerts
|

Early adverse experience increases emotional reactivity in juvenile rhesus macaques: Relation to amygdala volume

Abstract: This study investigated the impact of infant maltreatment on juvenile rhesus monkeys’ behavioral reactivity to novel stimuli and its associations with amygdala volume. Behavioral reactivity to novel stimuli of varying threat intensity was measured using Approach/Avoidance (AA) and Human Intruder (HI) tasks. In vivo magnetic resonance imaging (MRI) was used to measure amygdala volume. Interestingly, group behavioral differences were context-dependent. When exposed to a human intruder, maltreated subjects displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 81 publications
2
45
1
Order By: Relevance
“…Macaques exposed to SOR showed lower levels of distress during a developmental assessment compared to control animals [10]. Squirrel monkeys exposed to STS and macaques that experienced early life abuse showed increased exploratory behavior in the context of novel objects and environments [2,11,12]. These findings suggest that some benefits may derive from ELSA, such as increased resistance to the stress of novel nonsocial situations.…”
Section: Developmental Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Macaques exposed to SOR showed lower levels of distress during a developmental assessment compared to control animals [10]. Squirrel monkeys exposed to STS and macaques that experienced early life abuse showed increased exploratory behavior in the context of novel objects and environments [2,11,12]. These findings suggest that some benefits may derive from ELSA, such as increased resistance to the stress of novel nonsocial situations.…”
Section: Developmental Outcomesmentioning
confidence: 99%
“…Abused infant macaques display deficits in emotional expression such as the use of inappropriate vocalizations in response to contact and non-contact aggression [13]. Abused infants also exhibit high rates of distress vocalizations and anxiety-related behavior during normal social interactions, and in response to stressors and high-fear stimuli (animated toy accompanied by sounds) [11,14]. However, abused macaques show reduced anxiety-related behavior when exposed to low-fear or neutral stimuli (roll of tape) [11].…”
Section: Developmental Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent NHP neuroimaging studies have demonstrated a positive correlation between abuse rates experienced during infancy and amygdala volume, as well as reduced white matter integrity in tracts important for behavioral and emotional regulation that were also associated with elevated levels of cortisol in abused infants (Howell et al, 2014, 2013). These findings parallel findings reported in maltreated humans and children exposed to extreme psychosocial deprivation as a consequence of institutional care.…”
Section: Cross-species Success Storiesmentioning
confidence: 99%